POLA MAKAN DAN REPRODUKSI IKAN TOR SPP. SEBAGAI DASAR BUDIDAYANYA - SULASTRI, SULASTRI; RACHMATIKA, I.; HARTOTO, D.I. (BERITA BIOLOGI, 1985)
SULASTRI, I. RACHMATIKA & D.I. HARTOTO. 1985. Feeding and reproductive patterns of Torspp. as a base for its aquaculture. Berita Biologi 3(3): 84 -90. A study on the feeding and reproductive characteristics of Tor spp. as a base for aquaculture was done in laboratory and field conditions. Qualitative observation on the feeding habits of Tor douronensis (C.V.) do not show a restriction of the main diet to autochthonous sources. Algae were the main diet, followed by detritus, insects, diatoms, plant material, mosquitoes larvae and desmids. Laboratory observations show that T. douronensis eat first the food that is most concentrated, followed by the food that floats on the surface and last, foods on the bottom. Spearman Rank Correlation reveals that there was food overlaps between groups of fishes of different maturity stages from species collected in the field. It was found that there was a morphological change of male T. soro and a decrease of condition factors that were correlated with the increase of maturity stage. Vision as a significant factor affecting feeding and reproduction of Tor spp. and its relation to aquaculture application was discussed.